Unmanned Aerial Vehicles (UAVs): A Survey on Civil Applications and Key Research Challenges - Shakhatreh H.; Sawalmeh A.H.; Al-Fuqaha A.; Dou Z.; Almaita E.; Khalil I.; Othman N.S.; Khreishah A.; Guizani M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antennas; Contracts; Precision agriculture; Remote sensing; Civil infrastructures; Delivery of goods; Real time monitoring; Search and rescue; Security and surveillances; Wireless coverage; Unmanned aerial vehicles (UAV)